Analisis Sengketa PHPU Pilpres Tahun 2024 dalam Perspektif Hukum Progresif: Studi Kasus Putusan MK No: 1/PHPU.PRES-XXII/2024 - Pebrianto, Roli; Syarif Dahlan (Jurnal Risalah Kenotariatan, 2024)
This article aims to analyze the legal considerations in the Constitutional Court Decision Number: 1/PHPU.PRES-XXII/2024 related to the 2024 presidential election dispute. The analysis focuses on two main issues: first, the judges' considerations in deciding the case, and second, the application of progressive legal theory in the Court's considerations. This research uses a normative method with a statute approach and case approach, utilizing the Decision as primary legal material and legal literature as secondary material. The results show that the Constitutional Court delivers a final and binding decision, however, its judges tend to overlook moral and ethical aspects, sticking to positive law without progressive steps in considering societal values.